Epilepsy surgery of "low grade epilepsy associated neuroepithelial tumors": A retrospective nationwide Italian study. (14th August 2017) - Giulioni, Marco; Marucci, Gianluca; Pelliccia, Veronica; Gozzo, Francesca; Barba, Carmen; Didato, Giuseppe; Villani, Flavio; Di Gennaro, Giancarlo; Quarato, Pier Paolo; Esposito, Vincenzo; Consales, Alessandro; Martinoni, Matteo; et al.
Summary: Objective: To analyze the attitude and results of Italian epilepsy surgery centers in the surgical management of "low grade epilepsy associated neuroepithelial tumors" (LEATs). Methods: We conducted a retrospective study enrolling 339 consecutive patients with LEATs who underwent surgery between January 2009 and June 2015 at eight Italian epilepsy surgery centers. We compared demographic, clinical, pathologic, and surgical features of patients with favorable (Engel class I) and unfavorable (Engel class II, III, and IV) seizure outcome. In addition, we compared patients with tumor‐associated focal cortical dysplasia (FCD) and patients with solitary tumors to identify factors correlated with FCD diagnosis. Results: Fifty‐five (98.2%) of 56 patients with medically controlled epilepsy were seizure‐free after surgery, compared to 249 (88.0%) of 283 patients with refractory epilepsy. At multivariate analysis, three variables independently predict unfavorable seizure outcome in the drug‐resistant group. Age at surgery is largely the most significant (p = 0.001), with an odds ratio (OR) of 1.04. This means that the probability of seizure recurrence grows by 4% for every waited year. The resection site is also significant (p = 0.039), with a relative risk (RR) of 1.99 for extratemporal tumors. Finally, the completeness of tumor resection has a trend toward significance (p = 0.092), with an RR of 1.82 for incomplete resection. Among pediatric patients, a longer duration of epilepsy was significantly associated with preoperative neuropsychological deficits (p < 0.001). A statistically significant association was observed between FCD diagnosis and the following variables: tailored surgery (p < 0.001), temporal resection (p = 0.001), and surgical center (p = 0.012). Significance: Our nationwide LEATs study gives important insights on factors predicting seizure outcome in refractory epilepsy and determining variability in FCD detection. Timely surgery, regardless of pharmacoresistance and oriented to optimize epileptologic, neuropsychological, and oncologic outcomes should be warranted.